'Responsibility', change, and rising powers' role conceptions: comparing Indian foreign policy roles in global climate change negotiations and maritime security. (6th December 2018) - Plagemann, Johannes; Prys-Hansen, Miriam
Abstract: Strong economic growth and assertive political leadership have made India an increasingly prominent player in global governance. Whereas conventional scholarship of India's foreign policy underlines continuity, this article explores how India's self-conception has changed across two policy fields (climate change and maritime security). Adopting a role-theoretical approach, we analyze official statements as a mirror of both India's self-understanding and its view on the roles of significant other actors. Although both issue-areas exhibit change, India's self-ascribed role has been transformed more profoundly in the maritime domain. Our comparison suggests three factors to particularly induce transformation of rising powers' roles toward 'more responsibility': First, power-sharing is more conducive than burden-sharing; second, issue-areas with strong regional anchors are more likely to induce the adoption of a more responsible role than those areas situated primarily at the global level of politics; and third, positive external role ascriptions are more effective than negative ones.